Application of Cooperative Learning Type of Numbered Heads Together (NHT) to Increase Interest and Learning Outcomes in Economic Activities - Iman; Maulana, Panji; Akbar, Aulia (International Conference on Elementary Education, 2022)
This research is motivated by the low interest and learning outcomes of students in social studies learning material on economic activities. To overcome this, the researchers conducted research by applying NHT type cooperative learning. The purpose of this research is to increase students' interest and learning outcomes in social studies learning material on economic activities. The method used in this research is Classroom Action Research (CAR). This research was conducted on students in grades IV-A which was carried out in two cycles, where each cycle consisted of four stages, namely planning , action , observation , and reflection.. The instruments used are teacher performance observation sheets, teacher interview sheets, learning interest observation sheets, learning interest questionnaires, and social studies learning outcomes test sheets. Students' interest in learning is based on observations and questionnaires, the initial conditions are 39.5%, the first cycle is 75.5% and the second cycle is 87.1%. The increase in learning interest from the initial condition to the first cycle was 36%, while the increase from the first cycle to the second cycle was 11.6%, the total increase was 47.6%. These results show a significant increase. Student learning outcomes, the initial conditions showed 35% of students who completed, in the first cycle increased to 70% and the second cycle to 95%. The increase in learning outcomes from the initial conditions to the first cycle was 35%, while the increase from the first cycle to the second cycle was 25%, the total increase was 60%. Thus, it can be concluded that the application of cooperative learning of the NHT type in social studies subjects for economic activities can increase the interest and learning outcomes of grade IV-A students at SDN Cilembu, Pamulihan District, Sumedang Regency.